Model za učinkovito upravljanje proizvodnje po naročilu - Palčič, Iztok (Strojniški vestnik, 2003)
Customers are becoming increasingly more selective, and their requirements are harder to fulfil. This is why an order-based production, with its customisation to meet customers requirements, is becoming of great importance.The theoretical part of this paper presents the basic characteristics of this type of production and some of the main requirements and obstacles for effective planning and control. In addition, research is presented with results that add to the building of a new model for the succesful planning and control of order-based production. The research was performed in two Slovenian companies. The last section presents the structure of a proposed model and the requirements that a company has to fulfil in order to plan and control its production effectively.
Keywords: proizvodni sistemi; načrtovanje; organizacija proizvodnje; management; upravljanje; naročila